1988
DOI: 10.1101/gad.2.5.528
|View full text |Cite
|
Sign up to set email alerts
|

The mouse albumin promoter and a distal upstream site are simultaneously DNase I hypersensitive in liver chromatin and bind similar liver-abundant factors in vitro.

Abstract: In this paper we characterize the chromatin structure and nuclear proteins associated with different transcriptional states of the mouse serum albumin gene. We found the albumin gene to be transcribed in liver at rates 1000-fold or greater than in other tissues tested. We discovered seven DNase I hypersensitive sites encompassing the albumin gene only in liver chromatin, with strong hypersensitivity at the promoter and the enhancer, which is over 10 kb upstream. Using a gel retardation assay, we found a liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 73 publications
3
58
0
Order By: Relevance
“…1). Although others have reported that these condition-dependent differences in albumin expression are transcriptionally regulated and reflect differences in the protection of several DNasesensitive sites in regulatory elements of the albumin gene (36,37), differences in albumin mRNA expression are not associated with comparable differences in C/EBP mRNA expression ( Fig. 1).…”
Section: Rala255mentioning
confidence: 84%
See 1 more Smart Citation
“…1). Although others have reported that these condition-dependent differences in albumin expression are transcriptionally regulated and reflect differences in the protection of several DNasesensitive sites in regulatory elements of the albumin gene (36,37), differences in albumin mRNA expression are not associated with comparable differences in C/EBP mRNA expression ( Fig. 1).…”
Section: Rala255mentioning
confidence: 84%
“…Liu et al (37) reported that at least five distinct DNasesensitive sites in the albumin enhancer element are differentially protected in RALA255-like hepatocytes grown at permissive and restrictive temperatures. Our data suggest that some of the factors that bind to these other sites may be differentially expressed in RALA255 cells cultured at the two temperatures.…”
Section: Figmentioning
confidence: 99%
“…We previously showed that when H2.35 cells are shifted from a plastic to a collagen gel substratum, they exhibit a dramatic induction of serum albumin mRNA expression. 7 Albumin mRNA is transcribed solely in the liver, [58][59][60] so it serves as a classic marker of hepatocyte differentiation. Indeed, albumin mRNA and other liverspecific products decline markedly when hepatocytes are isolated from the liver and cultured on a plastic substratum, whereas albumin and other liver-specific mRNAs continue to be expressed at high levels when primary hepatocytes are cultured on collagen ECM gels.…”
Section: Deficient Albumin Mrna Expression In the ␣ 3 -Deficient Cellmentioning
confidence: 99%
“…DNase I Hypersensitivity Assays-The basic protocol has been described (40), and all preparatory steps were carried out at 4°C. Briefly, 1.5 to 2 ϫ 10 8 trypsinized cells were centrifuged at 2000 rpm for 10 min.…”
Section: Cells-a Set Of Matched P53mentioning
confidence: 99%